PENGARUH PREMI, KLAIM DAN HASIL INVESTASI TERHADAP LABA PADA PERUSAHAAN ASURANSI JIWA SYARIAH DI INDONESIA TAHUN 2014-2019 - Zen, Nia Anggraina; Manda, Gusganda Suria (Buletin Studi Ekonomi, 2021)
This study aims to determine the effect of premiums, claims and investment returns on the profits of Islamic life insurance companies in 2014-2019. The population used in this study is a sharia life insurance company registered with the Otoritas Jasa Keuangan (OJK) in the period 2014-2019 with a sampling method using purposive sampling techniques and gotted 9 sharia life insurance company samples were obtained that met the criteria for determining the sample. The data analysis method used in this study is multiple linear regression. The results of this study indicate that premiums have a positive effect on earnings, claims have no effect on earnings and investment returns have a positive effect on earnings.